2007
DOI: 10.1093/hmg/ddm133
|View full text |Cite
|
Sign up to set email alerts
|

Mutant huntingtin's effects on striatal gene expression in mice recapitulate changes observed in human Huntington's disease brain and do not differ with mutant huntingtin length or wild-type huntingtin dosage

Abstract: To test the hypotheses that mutant huntingtin protein length and wild-type huntingtin dosage have important effects on disease-related transcriptional dysfunction, we compared the changes in mRNA in seven genetic mouse models of Huntington's disease (HD) and postmortem human HD caudate. Transgenic models expressing short N-terminal fragments of mutant huntingtin (R6/1 and R6/2 mice) exhibited the most rapid effects on gene expression, consistent with previous studies. Although changes in the brains of knock-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
252
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 297 publications
(281 citation statements)
references
References 54 publications
(52 reference statements)
26
252
1
2
Order By: Relevance
“…A concordant coefficient was calculated, taking into account both concordant and discordant changes, as described previously (16) (SI Methods). The concordance coefficient for our dataset was 0.378 for down-regulated genes and 0.327 for all genes, which is consistent with previous studies reporting statistically significant concordance coefficients for other HD mouse models of 0.190 to 0.490 (with the related R6/1 and R6/2 lines equaling 0.350 and 0.405/0.490, respectively) (16). Hence, our findings indicate that R6/2 300Q transgenic mice exhibit expression profiles highly correlated with those observed in human HD.…”
Section: Hdaci 4b Treatment Ameliorates Gene Expression Abnormalities Insupporting
confidence: 92%
“…A concordant coefficient was calculated, taking into account both concordant and discordant changes, as described previously (16) (SI Methods). The concordance coefficient for our dataset was 0.378 for down-regulated genes and 0.327 for all genes, which is consistent with previous studies reporting statistically significant concordance coefficients for other HD mouse models of 0.190 to 0.490 (with the related R6/1 and R6/2 lines equaling 0.350 and 0.405/0.490, respectively) (16). Hence, our findings indicate that R6/2 300Q transgenic mice exhibit expression profiles highly correlated with those observed in human HD.…”
Section: Hdaci 4b Treatment Ameliorates Gene Expression Abnormalities Insupporting
confidence: 92%
“…Although the YAC128 mouse is one of the most comprehensive and well-established models of HD, no mouse model recapitulates all molecular manifestations of human HD. In fact, it is reported that YAC128 mice fail to show concordant gene expression changes with human HD until the mice are 24 mo of age (27), whereas our studies of altered HACE1 expression in YAC128 mice were restricted to mice 12 mo of age or younger. Additionally, in a recent study of 12 genes that were differentially expressed in the striatum of YAC128 versus control mouse striatum, only four of these 12 genes were concordantly changed when assessed in human HD versus control striatum (28).…”
Section: Hace1 Mediatesmentioning
confidence: 73%
“…To evaluate this hypothesis, we focused on H3K4 trimethylation (H3K4me3), a mark of transcription start sites (TSSs) and active chromatin (6-8). Growing evidence suggests that this mark is plastic and modulated in conditions of chronic stress, developmental disorders, psychiatric disorders (9-11) as well as during long-term memory consolidation from contextual fear conditioning (12), suggesting a critical function in brain.We first investigated H3K4me3 in the R6/2 mouse model of HD, which shows patterns of transcriptional dysregulation similar to postmortem HD brain (13,14). Using chromatin immunoprecipitation (ChIP), we examined H3K4me3 levels for Bdnf, which is expressed in the cortex, provides trophic support for GABAergic medium spiny neurons, and is expressed at lower levels in HD (5, 15).…”
mentioning
confidence: 99%
“…We first investigated H3K4me3 in the R6/2 mouse model of HD, which shows patterns of transcriptional dysregulation similar to postmortem HD brain (13,14). Using chromatin immunoprecipitation (ChIP), we examined H3K4me3 levels for Bdnf, which is expressed in the cortex, provides trophic support for GABAergic medium spiny neurons, and is expressed at lower levels in HD (5, 15).…”
mentioning
confidence: 99%